KAJIAN KARAKTERISTIK DAN EVALUASI PRODUKSI TERNAK KAMBING BERDASARKAN INDIKATOR KETERSEDIAAN PAKAN DI KABUPATEN MUNA BARAT - Irwansyah Irwansyah; Takdir Saili; La Ode Nafiu (Jurnal Ilmu dan Teknologi Peternakan Tropis, 2016)
West Muna regency is quite potential for development of livestock goats. However, the productivity level of goat in every region of West Muna regency and support of animal feed resources have been unknown for sure, therefore detailed information about the potential of animal feed resources is needed to be able fulfill production needs before developing goat farms. This study aimed to calculate the carrying capacity of goat farm based on the availability of animal feed in 18 villages within 6 sub-regencies including Kusambi, Napano Kusambi, Lawa, Central Tiworo, South Tiworo, and Tiworo Islands based on a criteria of population ownership. Primary data were collected from 101 respondents with a total of 408 animal units. The availability of animal feed was calculated by multiplying production of animal feed with harvested area and was expressed in dried materials (BK) and organic materials (BO). Samples of the production of green animal feed was obtained by taking grass from protected square meter and agricultural by products. Production of green legumes was calculated based on the production of each tree multiplies with harvested green area. Result of the study showed that with the current production of animal feed it is still possible to develop goat farm up to 359.52 UT/ha (2.247 animal units) or 227.5 UT cow per hectare. Keywords: production of goats, animal feed, carrying capacity